EARLY DIAGNOSIS OF MUSCULAR-JOINT DYSFUNCTION OF THE TMJ WITH THE HELP OF A COMPUTER ADDITIONAL PROGRAM - Kostiuk, Tatуana; Kaniura, Oleksandr (The Ukrainian Scientific Medical Youth Journal, 2019)
A topical issue of modern dentistry is the timely diagnosis and treatment of musculoskeletal syndrome of the temporomandibular joint (TMJ). A large number of publications in domestic and foreign literature is devoted to the study of this problem, but there is no single approach to diagnosis and a clear method of examination of the patient to establish a diagnosis. The purpose of our study was to implement a comprehensive methodology for early diagnosis of dysfunction by applying an analysis of a computer expert application we created. Based on the conducted research, in order to synchronize the data, simplify the work and deepen the analysis of diagnostics, an expert computer system for the diagnosis of dysfunction of the TMJ «PR» was developed. The program is applied and has 486 qualitative and quantitative components of the analysis criteria in its analytical base. The necessary parameters of the analysis include: frequency and intensity of headache, unilateral tinnitus, feeling of fatigue of chewing muscles during chewing solid food, degree of mouth opening, nature of movement of the mandible when opening the mouth, results of physical examination methods, the presence of clicks in the TMJ with taking into account the phase of mouth opening etc. s well as quantitative parameters of these additional methods of investigation of infrared thermography of the chewing muscles and area of the TMJ, EMG of chewing and mimic muscles, axiography, MRI, CT, ultrasound, digital analysis of occlusal ratios. The expert system program developed took into account all the maximum possible values of each parameter. The diagnosis was based on a combination of parameter values. The use of the multi-link expert computer system «PR» made it possible to take into account all the parameters of the patient examination and to obtain the most reliable diagnosis, which is necessary both at the initial stage of the patient’s treatment, and for correlation and correction of medical measures in such patients.